2013
DOI: 10.1016/j.ecolecon.2012.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Ecological macroeconomics: An application to climate change

Abstract: Ecological Economics has not paid sufficient attention to the macroeconomic level both in terms of theory and modelling. Yet, key topics debated in the field of Ecological Economics such as sustainable consumption, reduction in working time, the degrowth debate, the energy-exergy link, and the rebound effect require a wholistic and macro perspective. While this deficiency has been identified before and Keynesian economics has been generally suggested as a potent vehicle to establish economic system's thinking,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 51 publications
1
48
0
3
Order By: Relevance
“…The result is that the capital stock continues to expand, even as GDP growth stagnates, albeit at a slower rate than previously. Higher labor costs in the downshifting scenario stimulate investment in labor-saving technology, again as anticipated by Rezai et al (2013). The effect can be seen in the graph of manufacturing labor productivity growth shown in Figure 7.…”
Section: Model Behavior In Alternative Scenariosmentioning
confidence: 52%
See 3 more Smart Citations
“…The result is that the capital stock continues to expand, even as GDP growth stagnates, albeit at a slower rate than previously. Higher labor costs in the downshifting scenario stimulate investment in labor-saving technology, again as anticipated by Rezai et al (2013). The effect can be seen in the graph of manufacturing labor productivity growth shown in Figure 7.…”
Section: Model Behavior In Alternative Scenariosmentioning
confidence: 52%
“…We examined consumer-led efforts to reduce working time and expenditure, independent of any government initiatives. Furthermore, by abstracting from the government and trade, we could study the potential rebound from downshifting, as identified by Rezai et al (2013). We did, indeed, observe some rebound as a smaller labor pool drove up wages, which then drove consumption expenditure and labor-saving technological innovation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nationale und internationale Klimaschutzpolitik konzentriert sich auf wachstumsabhän-gige Politikmaßnahmen und eine wachsende Zahl von Studien hinterfragen kritisch die Auswirkungen von stringenten Klimaschutzzielen auf die Entwicklungspfade von Volkswirtschaften, sowie die dabei zu erwartenden Rückkopplungen (vgl. Victor, 2008;Jackson, 2009;Jackson und Victor, 2011;Victor, 2012;Rezai et al, 2013).…”
Section: Einleitung Introductionunclassified